Going Beyond Position Statements: One Hospital's Successful Initiative to Implement Napping for Night Shift Nurses. (October 2021) - Geiger-Brown, Jeanne; Harlow, Ashleigh; Bagshaw, Brett; Sagherian, Knar; Hinds, Pamela S.
Background: Sleepiness during the night shift is associated with errors, accidents, injuries, and drowsy driving. Despite scientific evidence that supports brief naps to reduce sleepiness, and guidance documents from policy organizations, napping has not been widely implemented. Methods: An initiative to translate scientific evidence about napping was implemented in one hospital over one year. The initiative included garnering leadership support and resources, building a translation team, evaluating the evidence, responding to operational concerns, developing an implementation strategy, and then implementing and evaluating the results. Night shift nurses were surveyed pre and post nap implementation for drowsy driving, sleepiness, and work and coworker relationships. Qualitative data documented the nurses' perceptions about napping. Findings: Three-fourths of the units that were eligible to nap successfully implemented and sustained napping. Most nurses felt refreshed by a brief nap and felt safer on the drive home, but one-fourth worried about or had sleep inertia symptoms. Drowsy driving remained unacceptably high. Conclusion: The initiative was successfully implemented on most nursing units. The mixed reaction to napping, and the unfavorable drowsy driving outcome point to the need for additional interventions to reduce sleepiness.